Kinerja Pengering dan Karakteristik Penepungan Daun Singkong (Manihot esculenta C) - Demato, Pingkan Najua; Suharyatun, Siti; Tamrin, Tamrin; Warji, Warji (Jurnal Agricultural Biosystem Engineering, 2025)
Cassava is one of the agricultural products that is abundant in Indonesia. The potential for cassava processing is very large along with the development of industry and leaving waste in the form of cassava leaves whose utilization is still limited. Cassava leaves are green vegetables that have nutritional content of protein, vitamins, and minerals. However, cassava leaves have the characteristic of being easily damaged because cassava leaves have a highwater content, allowing enzyme activity to occur. This causes cassava leaves not to be utilized optimally even though cassava leaves have a high protein content. Drying using a convection oven is an effective way to increase shelf life. The use of a hybrid dryer is an effective choice for drying cassava leaves. Material testing using electricity and solar power (hybrid) is carried out for 6 hours. Material testing using an oven is carried out for 4 hours. Testing using direct solar power (traditional) is carried out by drying for 6 hours. Proximate analysis is one method that has often been used to determine the nutritional content of raw materials or food. From the results of testing the proximate content of cassava leaf flour using a hybrid dryer, it was obtained; water content 3.18%, ash content 4.92%, fiber content 13.12%, protein 20.06%, fat content 5.18%, and BETN 66.66%. Drying using an oven, namely, water content 5.96%, ash content 5.99%, fiber content 15.72%, protein 16.132%, fat content 4.35%, and BETN 67.58%. Drying using solar energy (traditional), namely, water content 6.94%, ash content 4.98%, fiber content 16.48%, protein 16.84%, fat content 3.66%, and BETN 67.58%.